Sebastián - Kessler, Gabriela (Kessler, Gabriela ; Goldsmiths College, 2006)
Verzio FF Submission Cotita’s siblings are among the 30000 who went missing during Argentina’s bloodiest dictatorship in the late 1970s. Her brother (along with his partner who was pregnant) and her sister (also pregnant) were seized and killed by the military junta in power. Their bodies were never recovered. Cotita has spent the last twenty years trying to locate her siblings’ children, born in captivity. In February 2006, she finally found her brother’s son, Sebastián.